Transfronterizx Family, Their Children, and U.S. Educators in Border Communities - Sobeida Velázquez (Social Sciences)
Transfronterizx students and their families cross the U.S.–Mexico border daily for academic, economic, social, cultural, and linguistic reasons. Socioeconomic disparities, deportation, and work have propelled some families to live in Mexico and enroll their U.S.-born children in U.S. schools. Educators of transfronterizx students are uniquely tasked to work with these nontraditional students. This qualitative study aimed to understand the experiences of transfronterizx public school students, families, and educators of transfronterizx to understand the impact of transfronterizx students on strategies that support and foster effective family engagement. Findings include district and school policies that validate the experiences of people of color; transfronterizx community cultural wealth, including endurance and sacrifice wealth; and educators’ commitment to social justice through humanizing practices. Key themes include the following: fear is endemic among transfronterizx; the intersectionality of the global north and south shapes their experiences and interactions with the educational and sociopolitical systems. Lastly, I delineate recommendations for future research on the multilevel systems that impact transfronterizx.